A8.32 Tocilizumab contributes to the resolution of inflammation by affecting the migratory behaviour of monocytes in the synovial lining. (13th February 2015) - Byrne, RA; von Dalwigk, K; Steiner, G; Smolen, JS; Kiener, HP; Scheinecker, C
Abstract : Background: Monocytes (Mo) are among the first hematopoietic cells to migrate into the inflamed synovial tissue where they integrate into the synovial lining network of fibroblast-like synovial cells (FLS). Here we analyse the dependence of Mo – FLS interaction on proinflammatory cytokines and the effect of anti-IL-6 antibody (Ab) Tocilizumab using real time confocal/multiphoton microscopy of 3D micromass tissue cultures. Methods: Human FLS were prepared from synovial tissues obtained as discarded specimens following joint arthroplasty. CD14 + Mo were isolated from peripheral blood by magnetic bead sorting. For confocal imaging fluorescent labelled FLS and Mo were cultured in spherical extracellular matrix micromasses. Micromass cultures were set up in the presence of Tocilizumab or control Ab and stimulated with TNF-alpha. The resulting 4D live cell imaging movies were analysed with Imaris ® Software. Results: The highest migratory activity of Mo was observed on days 4–7 of culture, upon the formation of a FLS lining layer around a 3D micromass, The presence of Tocilizumab in TNF-alpha stimulated cultures i) increased the proportion of migrating Mo from 12% in control cultures to 22%, ii) increased the maximum track length of migrating monocytes and iii) stimulated a fast oscillating movement pattern of Mo. Conclusions: The 3D synovial tissue culture system allows for monitoring and analyses of subtle migration patterns of Mo in relation to the organised synovial lining architecture that depends on the presence of proinflammatory cytokines. Tocilizumab causes significant changes in the migratory behaviour of Mo that might lead to the release of Mo from the inflamed synovial tissue and contribute to the dissolution of inflammation. Ongoing experiments will address the molecular mechanism (s) of Mo – FLS interaction as well as the cellular source and sequence of cytokine production in order to identify potential targets for future therapeutic interventions in arthritis.